Vertex 3-colorability of claw-free graphs - Kamiński, Marcin; Lozin, Vadim (Algorithmic Operations Research, 2007)
The 3-COLORABILITY problem is NP-complete in the class of claw-free graphs. In this paper we study the computational complexity of the problem in subclasses of claw-free graphs defined by forbidding finitely many additional subgraphs (line graphs and claw-free graphs of bounded vertex degree being examples of such classes). We prove a necessary condition for the polynomial-time solvability of the problem in such classes and propose a linear-time solution for an infinitely increasing hierarchy of classes that meet the condition. To develop such a solution for the basis of this hierarchy, we generalize the notion of locally connected graphs that has been recently studied in the context of the 3-COLORABILITY